2017
DOI: 10.1371/journal.pone.0179938
|View full text |Cite
|
Sign up to set email alerts
|

Wave intensity of aortic root pressure as diagnostic marker of left ventricular systolic dysfunction

Abstract: BackgroundSystolic left ventricular function strongly influences the blood pressure waveform. Therefore, pressure-derived parameters might potentially be used as non-invasive, diagnostic markers of left ventricular impairment. The aim of this study was to investigate the performance of pressure-based parameters in combination with electrocardiography (ECG) for the detection of left ventricular systolic dysfunction defined as severely reduced ejection fraction (EF).Methods and resultsTwo populations, each compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…There are many studies devoted to determining the relationship between the indicators of CAP and the risk of AKI and cardiovascular complications [6,8,9,14], but there are not enough works that would determine the significance of these indicators in the perioperative period. Some studies have identified a close direct correlation between CAP and AKI [15], but in our study we did not find such a relationship, possibly due to the small sample size.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies devoted to determining the relationship between the indicators of CAP and the risk of AKI and cardiovascular complications [6,8,9,14], but there are not enough works that would determine the significance of these indicators in the perioperative period. Some studies have identified a close direct correlation between CAP and AKI [15], but in our study we did not find such a relationship, possibly due to the small sample size.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…It is difficult to predict cardiac events (acute coronary syndrome (ACS) or arrhythmias (HR)) or acute kidney injury (AKI) based on the results of standard preoperative examination of patients with coronary artery disease (CHD). However, a number of studies have shown that this category of adverse effects was often associated with impaired organ perfusion in patients with increased central aortic pressure (CAP) and arterial stiffness (AF) [4,5,6]. And these indicators with a sufficient degree of reliability can be assessed by non-invasive methods and do not require significant labor costs [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The method used to derive the flow velocity waveform from the measured pressure has some similarities with the approach used to derive flow waveforms in the ARCSolver method, which is based on a 3-element Windkesel model plus a minimal work criterion (Hametner et al, 2013). The ARCSolver method has been reported to outperform a simple triangular flow assumption in terms of pressure separation (Hametner et al, 2013), and it has been used for wave intensity analysis in one study (Hametner et al, 2017), although we are not aware of any validation studies using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works found that AP and AIx are lower for patients with systolic heart failure (SHF) as well as reduced EF, which is one of the main characteristics of SHF. 16,36,37 Possible reasons for this decrease in AP and AIx are changes in HR and ED. 16 Additional to a decreased contractility, heart failure with reduced ejection fraction (HFrEF) is often accompanied with a dilated ventricle.…”
Section: Discussionmentioning
confidence: 99%